Investigating 9d/8d non-supersymmetric branes and theories from supersymmetric heterotic strings - Yuta Hamada; Arata Ishige (Journal of High Energy Physics)
Abstract We consider heterotic string theories in nine and eight dimensions. We identify the disconnected part of the spacetime gauge group by studying the outer automorphism of the charge lattices. The absence of the global symmetry indicates the existence of non-supersymmetric codimension two branes. Moreover, we provide a list of gauge groups and matter contents of non-supersymmetric rank-reduced heterotic string theories (a branch corresponding to the E 8 string on S 1) from the orbifolding of the outer automorphism as well as the fermion parity. We also provide examples in eight dimensions.